Progress in nano-drug delivery of artemisinin and its derivatives: towards to use in immunomodulatory approaches - Charlie-Silva, Ives; Fraceto, Leonardo Fernandes [UNESP]; Silva de Melo, Nathalie Ferreira (Taylor & Francis Ltd, 2018)
In recent years, artemisinin (ART) and its derivatives have highlighted according to their effects on highly aggressive cancers, as well as treatment of malaria and leishmaniasis, besides presenting anti-inflammatory and antibacterial activity. It has also been shown that ART compounds have the ability to modulate the immune response by regulating cell proliferation and cytokine release. These effects may be beneficial and improve the treatment of cancer and parasitic diseases by increasing therapeutic success, but it has some pharmacological limitations such as low bioavailability, short half-life and limited tissue access. Nanotechnology has been explored during the last decades, notably in the design of drug carrier systems which includes polymeric, lipid and inorganic nanoparticles, cyclodextrins inclusion complexes, liposomes, carbon nanotubes, among others. These nanostructured drug delivery systems bring benefits both increased therapeutic efficacy and reduced toxicity. This review article aims to give an overview of the current progress in nanostructured drug carriers used for encapsulation of ART and its derivatives yielding examples of successful outcomes. The data collection suggests future applications of ART and derivatives encapsulated in nano delivery systems in clinical trials and prospects for use of ART loaded nanosystems in immunomodulatory responses.
Keywords: Artemisia annua; artemisinin; immune response; nanoparticles; drug delivery